Implementasi Pemberdayaan Kelompok Tani Perspektif Hukum Ekonomi Syariah - Mario Rizaldi; Jefik Zulfikar Hafizd; Akhmad Shodikin; Ahmad Khoirudin (STAI Al-Mas'udiyah, 2025)
Agriculture is one of the sectors that can improve welfare for the community, the government has regulated the implementation of empowerment in the agricultural sector, both individually and in farmer groups. The research aims to be able to find out the implementation of community economic empowerment in farmer groups in Kudukeras Village, Babakan District, Cirebon Regency can improve the welfare of farmer group communities, the implementation of empowerment carried out whether it has used the principles of Sharia Economic Law. The method used in this research uses descriptive qualitative which is a case study on farmer groups in Kudukeras Village. The data collection technique uses a triangulation method consisting of interviews, observations, and documentation. The results of this study are first, that the empowerment of farmer groups in Kudukeras Village has been running as stated in the empowerment theories and regulations of the Minister of Agriculture and Law Number 19 of 2013 consisting of counseling, training, discussion, and field practice. Secondly, the implementation of empowerment of farmer groups has practiced the principles of Sharia economic law itself.